EDUCTIVE ABILITY IN ADOLESCENT STUDENTS FROM BUENOS AIRES: A LONGITUDINAL STUDY - Fernández Liporace, Mercedes; Varela Mallou, Jesús; Martina Casullo, María; Rial Boubeta, Antonio (Anales de Psicología / Annals of Psychology, 2003)
Data gathered from 104 adolescent subjects of both sexes, from Buenos Aires, Argentina, assessed in a test – retest procedure with a short version of Raven´s Standard Progressive Matrices, are analyzed in a longitudinal study. Subjects were 8th gradrers at the first measuring moment (1994; mean age= 13) and Senior High School students at retest moment (1998; mean age= 17). Results verified a significant gain of raw scores between test and retest, associated with sex and with parental educational and occupational level. Discussion focuses in school role on eductive ability development.